Increasing tactical complexity to enhance the synchronisation of collective behaviours: An action-research study throughout a competitive volleyball season - Ramos, A.; Coutinho, P.; Ribeiro, J.; Fernandes, O.; Davids, K.; Mesquita, I. (Journal of Sports Sciences, 2020)
An Action-Research (AR) design was implemented throughout a competitive season in which Constraint-led and Step-Game approaches were combined. This intervention study investigated the impact of increased performance complexity on emergence of counterattacking synchronisation tendencies in team players (laterally and longitudinally on court) at different set moments. Fifteen youth volleyball team players were studied across three action-research cycles, with performance in one competitive match analysed per cycle. Team synchronisation tendencies were assessed using the cluster phase method, with a 3 (matches) x 2 (set moments) x 2 (court direction) repeated-measures ANOVA statistical procedure to calculate differences in cluster amplitude mean values. Results revealed a reduction in team synchrony levels when tactical complexity of counterattacking play increased (second AR-cycle). Nevertheless, similar levels of team synchrony emerged between the first and third AR-cycles. Results also revealed the final moments of a set as a significant environmental constraint that shaped synchronisation tendencies. Evidence suggested that the (re)achievement of functional synchrony was realised through integration of Constraint-led and Step-Game approaches during practices designed to enhance tactical awareness in players. Finally, an insider action-research design provided relevant contextualised insights on the development of a team`s synchronisation tendencies.